Faktor-Faktor yang Mempengaruhi Minat Konsumen Terhadap Daging Asap - Muhammad Mas Multazam; Agung Tryasnandi; Dewi Turgarini; Caria Ningsih (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2022)
Covid-19 or the corona virus disease has had a very significant impact on the economy and business, especially the food and beverage industry. Starting a new business again requires some adjustments, one of which is the new normal lifestyle. One of the new habits or adjustments that occur in the food and beverage industry is the rise of frozen ready-to-eat foods or frozen food. This is due to changes in consumer behavior in the food industry, which initially eats out to eat at home more often. By consuming frozen ready-to-eat food or frozen food, consumers feel healthier and safer from the covid-19 virus. This study aims to: 1). Identify factors that influence the purchase of frozen food 2). Knowing the frozen food consumer market segmentation. The research method used in this research is descriptive quantitative with the method of observation, questionnaires and literature study. The results of previous studies indicate that the factors that influence the purchase of frozen food, among others, because it is easy to cook and safe, brand image, quality, low price, advertising, appearance, availability, and taste.